2012
DOI: 10.1590/s2237-93632012000400002
|View full text |Cite
|
Sign up to set email alerts
|

Role of bowel preparation on colocolonic anastomosis: experimental study in dogs

Abstract: 0.05). CONCLUSION: Colocolonic anastomosis without previous bowel preparation was shown to be safe and efficacious, suggesting it is not an indispensable procedure in colorectal anastomosis surgery.]]>

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0
1

Year Published

2015
2015
2016
2016

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 13 publications
0
5
0
1
Order By: Relevance
“…While anastomosis defects at postoperative day 9 were seen in 13% of dogs undergoing MBP, this rate was 47% in those not receiving MBP; the authors concluded that MBP could actually increase the rate of complications. In 2012, Regadas et al [ 11 ] reported a study of 42 dogs that were separated into 2 groups. The authors found no difference in anastomosis bursting pressure at postoperative day 21 between dogs undergoing MCT and those who did not.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While anastomosis defects at postoperative day 9 were seen in 13% of dogs undergoing MBP, this rate was 47% in those not receiving MBP; the authors concluded that MBP could actually increase the rate of complications. In 2012, Regadas et al [ 11 ] reported a study of 42 dogs that were separated into 2 groups. The authors found no difference in anastomosis bursting pressure at postoperative day 21 between dogs undergoing MCT and those who did not.…”
Section: Discussionmentioning
confidence: 99%
“…While our study shows similarities to the study by Mersin et al [ 10 ], we also performed histopathological examination of anastomosis site tissues. The 3 studies previously mentioned in this paragraph [ 10 , 11 , 16 ] all examined anastomotic bursting pressure as a measure of anastomosis safety. Although O’Dwyer et al [ 18 ] found a significant decrease in anastomotic leakage pressure in animals not undergoing MBP, Regadus et al [ 11 ], Mersin et al [ 10 ], and the present study found no difference in bursting pressure between the groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Preoperative (24 hours) fasting showed that was not sufficient for proper bowel preparation 21 , and many related substances might have better results, such as polyvinylpyrrolidone 22 and retrograde flushing 23 . The findings from this study suggest that fasting might be substituted by other techniques for gastrointestinal cleansing.…”
Section: Discussionmentioning
confidence: 99%
“…Ряд хирургов считают её обязательной процедурой [64,76]. В то же время, немало сообщений, где не было обнаружено разницы в частоте несостоятельности анастомозов, инфекционных осложнений, сроках пребывания в стационаре между больными, получавшими механическую очистку кишечника и больным без подготовки [46][47][48]64,65], с другой стороны, существуют многочисленные публикации об эффективности механической очистки кишечника в эксперименте у животных [54,57,61]. Было изучено отношение к механическим анастомозам с помощью степлеров 241 хирургов-гастроэнтерологов в Японии [49].…”
unclassified